Islamic teaching stress coping strategies: Do primary school deputies practiced? - Tahir L.M.; Musah M.B.; Samah N.A.; Jaffri H.; Talib R.; Yusof S.M.; Yassin M.A.-M.; Said A.M. (Serials Publications, 2024)
This study investigates deputy headteacher's stress and coping strategies while leading schools in the context of Malaysia. Deputy headteacher stress studies date back as early as 1990s, but less explored in Malaysia. Using sequential mixed methods approach, the study sampled 120 Muslim deputy headteachers and further interviewed another 21 deputies to investigate the Islamic religious-based stress-solving approaches that deputies employed in coping with stress experiences. The findings revealed that deputies' stress was considered as low through their Islamic coping strategies such as frequently pray to Allah, performing dhikr and reciting Yassen while experiencing stress. Implications for policymakers and school heads were also discussed. Serials Publications.